Equatorial Ionospheric Response to Different Estimated Disturbed Electric Fields as Investigated Using Sheffield University Plasmasphere Ionosphere Model at Inpe - Bravo-Gonzalez, M (Blackwell Publishing Ltd, 2017)
Good ionospheric modeling is important to understand anomalous effects, mainly during geomagnetic storm events. Ionospheric electric fields, thermospheric winds, and neutral composition are affected at different degrees, depending on the intensity of the magnetic disturbance which, in turns, affects the electron density distribution at all latitudes. The most important disturbed parameter for the equatorial ionosphere is the electric field, which is responsible for the equatorial ionization anomaly. Here various electric field measurements and models are analyzed: (1) measured by the Jicamarca incoherent scatter radar (ISR), (2) from Jicamarca Unattended Long-Term studies of the Ionosphere and Atmosphere (JULIA) radar, (3) deduced from magnetometers, (4) calculated from the time variations of the F layer height (dh′F/dt), and (5) deduced from interplanetary electric field determinations. The response of ionospheric parameters foF2 and hmF2 to the electric fields simulated using the Sheffield University Plasmasphere Ionosphere Model version available at Instituto Nacional de Pesquisas Espaciais is compared with observations for two locations, during the geomagnetic storm events of 17–18 April 2002 and 7–10 November 2004. Results are found to be consistent with the observations in such a way that a hierarchy among the different types of drifts used can be established. When no ISR measurements are available, the drifts deduced from magnetometers or measured by the JULIA are best when including the contribution derived from dh′F/dt for the 18–24 LT time interval. However, when none of these drifts are available, drifts inferred from the interplanetary electric field seem to be a good alternative for some purposes. ©2017. American Geophysical Union. All Rights Reserved.